IMPACT OF LIMITED ORAL ANTITUBERCULOSIS INFORMATION TO THE TUBERCULOSIS PATIENTSâ COMPLIANCE AND THEIR QUALITY OF LIFE - Handayani, Dian; Perwitasari, Diah Aryani (Universitas Ahmad Dahlan, 2013)
The study about impact of limited oral antituberculosis information delivered bypharmacist to patient compliance and their quality of life in two public health centers inYogyakarta has been carried out. This study was performed using cohort eventmonitoring design, with 14 pulmonary TB patients and positive Acid Resistant Basilwere treated with oral antituberculosis (OAT) for at least 1 month and were older than15 years old. We observed the compliance of one group of patients using oralantituberculosis who were serviced with OAT information and the other group withoutOAT information service. The patientsâ compliance was checked by counting theremaining OAT and by interviewing the patients, meanwhile patientâs quality of lifewere measured by SF-36 instrument. The correlation between limited OAT informationservice and patient compliance were analysed using Chi Square and quality of patientâslife were analysed using Independent t-Test with 95% confidence level. It was shownthat characteristics of patients such as age, gender, education, duration of illness, andDirectly Observed Treatment involvement did not influence patient compliance. Therewas no significant correlation between limited OAT information service to patientcompliance and patientsâ quality of life (P>0.05). There is no impact of limited OATinformation service to the TB patientsâ compliance and their quality of life. Wesuggested that the further and deeply information service delivered by pharmacists inthe public helath centers in Yogyakarta should be carried out.